2022
DOI: 10.1096/fj.202101698r
|View full text |Cite
|
Sign up to set email alerts
|

The metabolomic profiling identifies N, N‐dimethylglycine as a facilitator of dorsal root ganglia neuron axon regeneration after injury

Abstract: Identifying novel molecules involved in axon regeneration of neurons in the peripheral nervous system (PNS) will be of benefit in obtaining a therapeutic strategy for repairing axon damage both in the PNS and the central nervous system (CNS). Metabolism and axon regeneration are tightly connected. However, the overall metabolic processes and the landscape of the metabolites in axon regeneration of PNS neurons are uncovered. Here, we used an ultra high performance liquid tandem chromatography quadrupole time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Further, by using the classical UVB irradiation-induced model system, we also showed that DMG-Na significantly counteracted the effect of UVB irradiation to upregulate ROS production of epidermal keratinocytes. This corroborates well with previous studies that reported the profound antioxidant and scavenger actions of DMG and its sodium salt in practically all (extra-cutaneous) tissues measured so far [14][15][16][17][18][19][20][21][22][23], including the gastrointestinal tract [14][15][16], liver [17,18], skeletal muscle [19][20][21], and peripheral neurons [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, by using the classical UVB irradiation-induced model system, we also showed that DMG-Na significantly counteracted the effect of UVB irradiation to upregulate ROS production of epidermal keratinocytes. This corroborates well with previous studies that reported the profound antioxidant and scavenger actions of DMG and its sodium salt in practically all (extra-cutaneous) tissues measured so far [14][15][16][17][18][19][20][21][22][23], including the gastrointestinal tract [14][15][16], liver [17,18], skeletal muscle [19][20][21], and peripheral neurons [22].…”
Section: Discussionsupporting
confidence: 93%
“…Besides these effects, it has also been proposed that DMG and its sodium salt may function as a source of glycine for glutathione synthesis, and hence may improve cellular and tissue antioxidant capacities. Indeed, in various animal studies that model pathologies of, e.g., the gastrointestinal tract [14][15][16], liver [17,18], skeletal muscle [19][20][21], and peripheral neurons [22], both DMG and its sodium salt were shown to reduce oxidative stress damage by exhibiting scavenger activities against excess free radicals and to improve the utilization of oxygen [14][15][16][17][18][19][20][21][22][23]; hence, they can be conductive to the body's redox status and its regeneration and repair. Moreover, DMG, acting as a methyl donor, has been suggested to improve immunity and enhance immune responses [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Oviductal samples were prepared with reference to those mentioned in previous publications, with some modifications. 36 , 37 25 mg of oviduct tissue was weighed, and six biological replicates were used for each of the breeding season and pre-brumation. 500 μL extract solution (acetonitrile:methanol:water, 2:2:1) containing isotopically-labelled internal standard (L-2-Chlorophenylalanine) mixture was added.…”
Section: Methodsmentioning
confidence: 99%
“…However, single-cell multi-omics mainly focus on the CNS, and their application in the PNS is relatively limited. The methylation and metabonomics of DRG have been sequenced at the bulk level ( Weng et al, 2018 ; Zhang et al, 2022 ). Mapping these dates to single-cell transcriptomes may offer enlightenment to discover specific responded cell sub-types under naïve or disease states.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%